Experimental Investigation into the Characteristics of In-Pipe Leak Noise in Plastic Water Filled Pipes - Papastefanou, Anastasia S.; Joseph, Phillip F.; Brennan, Michael J. [UNESP] (S Hirzel Verlag, 2012)
This paper presents an experimental investigation of the characteristics of leak noise in plastic water-filled pipes. An experimental set-up was designed to identify the physical mechanisms of leak noise generation. Possible mechanisms include cavitation and turbulence. The experiments show that cavitation is not responsible for leak noise generation and clearly indicate that turbulence is the main mechanism, at least in the experiments conducted. An alternative experimental set-up was also designed to identify the characteristics of leak noise spectra and to investigate how the spectra are affected by the leak size and the leak flow velocity. A number of different hole sizes (leaks) starting from 1 mm diameter, increasing progressively every 0.5 mm until a size of 4 mm diameter were tested for different jet velocities and an empirical model that describes this behaviour is proposed.